O PAPEL DO MINISTÉRIO PÚBLICO NA EDUCAÇÃO AMBIENTAL POR MEIO DO TERMO DE AJUSTAMENTO DE CONDUTA - Ribeiro, Pablo da Costa; Araújo, Luiz Ernani Bonesso de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
The serious imbalances of nature by man are a matter of serious concern to environmentalists andeducators worldwide. To combat the ills that plague the environment emerged as pedagogical,Environmental Education whose goal is the dissemination of knowledge about the environmentwith the aim of assisting in the conservation and sustainable use of natural resources. However, inan interdisciplinary education, discipline needs to have allies in other fields of knowledge to assisther in this difficult task of awareness. The proposal for an ecopedagogy associated with the right,brings the concern to rescue a supervsor who has knowledge of the different branches ofeducation in a pluralistic approach, but not specialized. From that idea, presents itself as an ally ofEnvironmental Education to the national Public Ministry, public defender of law, the democratic regime and of individual interests unavailable. The interaction of environmental education with abody of work that court is the Public Ministry, from the education, may be by means of legalinstruments that the latter has in its body of law, if the term of conduct adjustment (TAC) whocomes to serve as a socio-educational effective to combat the excesses caused by man in nature.The TAC is the instrument of legal action hue education that Public Ministry can resort to helpenvironmental education in environmental protection.